PENGEMBANGAN MEDIA PEMBELAJARAN BERBASIS ANDROID PADA MATA PELAJARAN PENGENALAN MICRODOFT WORD DI LPK SHEZA PONTIANAK - Danar Santoso; Dochi Ramadhani (Universitas Negeri Padang, 2019)
The purpose of the study was to find out how the development of Android-based learning media for the LPK training and course institutions SHEZA, to find out the feasibility of Android-based learning media for LPK training institutions and SHEZA courses. Learning media is designed using the Pascal programming language with the application of Embacadero Delphi XE 8. The Android platform was chosen because all LPK Sheza students use an Android smartphone, the microsoft word learning media developed is an Android-based learning media. because Android-based devices have been widely used in communities from various circles. So that the use of mobile devices or smartphones among users is optimal especially for learning. The hope, this study can facilitate educators or students in particular to increase the spirit of learning and achieve its goals in learning. The study was conducted at LPK SHEZA. The type of research used is R & D research. The research was conducted in two stages. The first stage for product development uses the ADDIE model and the second stage. Data collection techniques use measurement and direct communication. The data collection tool uses an interview guide and questionnaire. The results of the study are the development of Android-based learning media for LPK training institutions and SHEZA courses worthy of use.